2021
DOI: 10.1007/s00384-021-03850-9
|View full text |Cite
|
Sign up to set email alerts
|

Ileo-colic intra-corporeal anastomosis during robotic right colectomy: a systematic literature review and meta-analysis of different techniques

Abstract: Purpose Robotic assistance could increase the rate of ileo-colic intra-corporeal anastomosis (ICA) during robotic right colectomy (RRC). However, although robotic ICA can be accomplished with several different technical variants, it is not clear whether some of these technical details should be preferred. An evaluation of the possible advantage of one respect to another would be useful. Methods We conducted a systematic review of literature on technical de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 53 publications
3
10
0
Order By: Relevance
“…The ICA approach, irrespective of technique, is associated with low rates of postoperative gastrointestinal dysfunction and earlier postoperative recovery. Our work demonstrates largely equivalent clinical outcomes between the two approaches, echoing previous works in this area [13], and supports broader works supporting superior clinical outcomes observed with ICA overall [14].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The ICA approach, irrespective of technique, is associated with low rates of postoperative gastrointestinal dysfunction and earlier postoperative recovery. Our work demonstrates largely equivalent clinical outcomes between the two approaches, echoing previous works in this area [13], and supports broader works supporting superior clinical outcomes observed with ICA overall [14].…”
Section: Discussionsupporting
confidence: 89%
“…This is supported by previous works, with Johnston et al reporting an anastomotic leak rate of 0.9% following stapled robotic ICA [21] and Guadagni et al reporting an anastomotic leak rate of 1.5% in handsewn robotic anastomosis [13]. The overall reported rates of anastomotic leak following robotic hemicolectomy are low, ranging from 0.9% to 3.1% [13,21–23]. In comparison, the reported anastomotic leak rates for open and laparoscopic right hemicolectomy are much higher, with the European Society of Coloproctology right hemicolectomy audit reporting anastomotic leak rates of 11.4% and 5.4%, respectively [2].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Recent studies have reported uniformly low rates of anastomotic leakage. The overall reported rates of anastomotic leak following robotic right colectomy are low, ranging between 0.9% and 3.8% [24][25][26]. Regarding SSI, theoretically, the intraperitoneal incision into the bowel lumen in IA may cause fecal spillage, which can lead to SSI.…”
Section: Postoperative Outcomesmentioning
confidence: 99%
“…Recent studies have reported uniformly low rates of anastomotic leakage. The overall reported rates of anastomotic leak following robotic right colectomy are low, ranging between 0.9% and 3.8% [ 24 - 26 ].…”
Section: Postoperative Outcomesmentioning
confidence: 99%